Differential Lipid Accumulation on HepG2 Cells Triggered by Palmitic and Linoleic Fatty Acids Exposure - Teixeira, Francisca S.; Pimentel, Lígia L.; Vidigal, Susana S. M. P.; Azevedo-Silva, João; Pintado, Manuela E.; Rodríguez-Alcalá, Luís M. (Molecules (Basel, Switzerland), 2023)
Lipid metabolism pathways such as β-oxidation, lipolysis and, lipogenesis, are mainly associated with normal liver function. However, steatosis is a growing pathology caused by the accumulation of lipids in hepatic cells due to increased lipogenesis, dysregulated lipid metabolism, and/or reduced lipolysis. Accordingly, this investigation hypothesizes a selective in vitro accumulation of palmitic and linoleic fatty acids on hepatocytes. After assessing the metabolic inhibition, apoptotic effect, and reactive oxygen species (ROS) generation by linoleic (LA) and palmitic (PA) fatty acids, HepG2 cells were exposed to different ratios of LA and PA to study the lipid accumulation using the lipophilic dye Oil Red O. Lipidomic studies were also carried out after lipid isolation. Results revealed that LA was highly accumulated and induced ROS production when compared to PA. Lipid profile modifications were observed after LA:PA 1:1 (v/v) exposure, which led to a four-fold increase in triglycerides (TGs) (mainly in linoleic acid-containing species), as well as a increase in cholesterol and polyunsaturated fatty acids (PUFA) content when compared to the control cells. The present work highlights the importance of balancing both PA and LA fatty acids concentrations in HepG2 cells to maintain normal levels of free fatty acids (FFAs), cholesterol, and TGs and to minimize some of the observed in vitro effects (i.e., apoptosis, ROS generation and lipid accumulation) caused by these fatty acids.